A Worldwide Bibliometric Analysis of Publications on Coronavirus in the Past 3 Decades: A Bibliometric Article - Te-Chun Yeh; Yu-Ching Lee; Ling-Fang Wei; Senyeong Kao; Chia-Jen Liu; Ju-O Wang (Tehran University of Medical Sciences, 2021)
Background: Coronaviruses caused three pandemics and impact public health globally in the 21st century. However, limited data were for the evaluation of the trend of coronavirus researches. We aimed to analyze quantitatively, qualitatively, and visually evaluate global scientific publications on coronavirus by using bibliometric analysis. Methods: Coronavirus-related research from 1990-2019 was retrieved from the Web of Science Core Collection database (WoS). Microsoft Excel and VOS viewer software were used to assess the characteristics of publications. Results: Overall, 9,553 publications on coronavirus were retrieved on 12 Mar 2020. The United States took a leading position in coronavirus-related research and accounted for more than one-thirds (36.7%) of all publications. The most productive journal in this field was Journal of Virology (1,056, 11.1%), and the most productive institution was University of Hong Kong (394, 4.1%). The main hot topics in coronavirus field were virus infection and protein. Active collaborations between countries were observed. Conclusion: Over the past three decades, coronavirus research has gradually increased due to two global outbreaks. Through this global bibliometric evaluation, some relevant evidence could be provided. Corresponding to the impact of novel coronavirus (COVID-19), a large number of articles can be expected to appear in the next few years, and international cooperation should be strengthened to solve the problem.